Literatura infantil: um recurso educativo para o desenvolvimento de crianças com Transtorno do Espectro Autista - Lacerda, Joyce Rayane Carvalho (2020)
This course conclusion paper deals with “Children's literature: an educational resource for the development of children with autism spectrum disorder; aimed to identify successful pedagogical strategies and practices in early childhood education through children's literature with autistic children. From a methodological point of view, it is an exploratory and descriptive research, with a qualitative approach; it was based on the theoretical contribution of studies by Gil (2002) and Prodanov; Freitas (2013) that best elucidate the proposal of this research. Thus, a survey was carried out with ten educators, six from public schools and four from private schools in the cities of Pombal-PB and Mossoró-RN. Therefore, I highlight the literature of RCNEI (1998), DSM-5 (2014), Abramovich (1997). The analysis of the data revealed that the practice of children's literature is very frequent with autistic children, that teachers see the resource as a tool for the child's development, contemplating social, emotional and cognitive aspects. In addition to being a stimulus for imagination, creativity, language and attention. Thus proving its importance in the school routine.